2016
DOI: 10.1007/s11207-016-0846-9
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Quasi-periodic Pulses in the Flare of 18 August 2012

Abstract: We analyzed spatial and spectral characteristics of quasi-periodic pulses (QPP) for the 18 August 2012 limb flare, using new data from a complex of spectral and imaging instruments developed by the Siberian Solar Radio Telescope team and the Wind/Konus gamma-ray spectrometer. A sequence of broadband pulses with periods of approximately ten seconds were observed in Xrays at energies between 25 keV and 300 keV, and in microwaves at frequencies from a few GHz up to 34 GHz during an interval of one minute. The QPP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The inverted bell shape of the spectra is typical for the gyrosynchrotron emission. Both spectra are flat in the 3.75-9.4 GHz range, which evidences the contribution to the emission of more than one source or, in a general case, of a spatial nonuniformity of the source (Lee & Gary 1994;Altyntsev et al 2016;Fleishman et al 2016b). The spectrum shapes are similar before and at the subpeak, but the difference is weaker at the optically thick part at low frequencies.…”
Section: Spectral Properties In X-ray and Microwave Emissionmentioning
confidence: 90%
“…The inverted bell shape of the spectra is typical for the gyrosynchrotron emission. Both spectra are flat in the 3.75-9.4 GHz range, which evidences the contribution to the emission of more than one source or, in a general case, of a spatial nonuniformity of the source (Lee & Gary 1994;Altyntsev et al 2016;Fleishman et al 2016b). The spectrum shapes are similar before and at the subpeak, but the difference is weaker at the optically thick part at low frequencies.…”
Section: Spectral Properties In X-ray and Microwave Emissionmentioning
confidence: 90%
“…In the preceding studies of microwave flare emissions, the sources observed by the SSRT at 5.7 GHz were typically associated with loop-top regions (e.g. Altyntsev et al, 2002Altyntsev et al, , 2007Altyntsev et al, , 2016Meshalkina et al, 2012, and others). In the 26 December 2001 flare, two distinct microwave sources were observed.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The usage of the SSRT data in studies of flares has been limited (e.g. Altyntsev et al, 2002Altyntsev et al, , 2007Altyntsev et al, , 2016Meshalkina et al, 2012;Alissandrakis et al, 2013). The 1D-mode observations of a higher time resolution have also been involved, especially in studies of microwave sources on short time scales.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction site, seen as the main source in hard X-rays and in microwaves, is located near the common footpoint of the loops. Recently such flares have been discussed by Altyntsev et al (2016) and . Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Gyrosynchrotron sources at high frequencies are often located close to the flare loop footpoints where the magnetic field exceeds several hundred Gauss, before lower frequencies are emitted from greater heights. Flares initiated by an interaction of two loops of rather different size have been reported (Hanaoka, 1997;Nishio et al, 1997;Altyntsev et al, 2016;. The NoRH polarization images at 17 GHz showed footpoints of a small loop and the SSRT observed a large loop at 5.7 GHz.…”
Section: Introductionmentioning
confidence: 88%